FACTORS AFFECTING THE DEVELOPMENT OF FOREST TOURISM CEMARA BEACH AND ITS IMPACT ON INCOME FARMER HOUSEHOLD - Gunawan, Ridwan; Dasipah, Euis; Dahtiar, Agi (Universitas Majalengka, 2024)
The objective of this study is to examine the factors that impact the growth of Cemara Beach Forest Tourism and its effect on the earnings of farmer households. The respondents were selected through the census method, with a total of 65 units. The approach employed for analysis was path analysis and paired t test. The study revealed that the attractiveness and tourism environment of Cemara beach forest, which includes Attractions, Amenities, Accessibility, and Auxiliary Services, had a good achievement level of 72.90%. Supporting Institutions for tourism also achieved a good criterion of 65.85%. Additionally, community participation showed good conditions with a good criteria achievement level of 61.92%. The development of Cemara Beach Forest Tourism attained a good criteria achievement level of 77.93%. Tourist Attraction and Environment had a positive correlation r = 0.89, indicating a very close relationship with Supporting Institutions. This suggests that the better the Supporting Institutions are, the better the Tourist Attraction and Environment. Community Participation demonstrated an indication of a very close relationship with Tourist Attraction and Environment. This implies that community participation increases with better tourist attractions and the environment. Supporting Institutions had a positive correlation r = 0.89 with community participation, indicating a close relationship. This implies that the better the Supporting Institutions, the better the community participation. Tourist Attraction and Environment, Supporting Institutions, and Community Participation had a positive effect on the development of Cemara beach forest tourism, with tourist attraction having the greatest influence at 46.85%, followed by Supporting Institutions at 25.82%, and Community Participation at 23.58%. The development of Cemara coastal forest tourism had a positive impact on the income of farmer households, increasing it by an average of 67.16%.